(untitled) (Sebha University Conference Proceedings, 2024)
The current research aims at identifying the healthy behaviour of diabetics at the diabetes clinic in Sabha City and indicating the differences in healthy behaviour depending on the variables of "sex, age", based on the descriptive approach of "sample survey", using the health behavior questionnaire prepared by the researchers on a sample based on (245) Diabetes patient, using a single sample T test, a Man and TN test, and a variation analysis test, the results show that the level of health behaviour of diabetics in the city of Sabha D is statistically above the hypothesis, except after (Mathematical behaviour) is not statistically D to a degree below hypothesis, and there are no statistically significant differences in all dimensions of healthy behaviour depending on sex and age.